Traffic jams and the complex role of α-Synuclein aggregation in Parkinson disease. (3rd April 2017) - Gonçalves, Susana A.; Outeiro, Tiago Fleming
ABSTRACT: A common pathological event among various neurodegenerative disorders (NDs) is the misfolding and aggregation of different proteins in the brain. This is thought to potentiate aberrant protein-protein interactions that culminate in the disruption of several biological processes and, ultimately, in neuronal cell loss. Although protein aggregates are a common hallmark in several disorders, the molecular pathways leading to their generation remain unclear. The misfolding and aggregation of α-Synuclein (aSyn) is the pathological hallmark of Parkinson disease (PD), the second most common age related ND. It has been postulated that oligomeric species of aSyn, rather than more mature aggregated forms of the protein, are the causative agents of cytotoxicity. In recent years, we have been investigating the molecular mechanisms underlying the initial steps of aSyn accumulation in living cells. Using an unbiased genome-wide lentiviral RNAi screen we identified trafficking and kinase genes as modulators of aSyn oligomerization, aggregation, and toxicity. Among those, Rab8b, Rab11a, Rab13 and Slp5 were found to promote the clearance of aSyn inclusions and reduce aSyn toxicity. Moreover, we found that endocytic recycling and secretion of aSyn was enhanced upon expression of Rab11a or Rab13 in cells accumulating aSyn inclusions. Altogether, our findings suggest specific trafficking steps may prove beneficial as targets for therapeutic intervention in synucleinopathies, and should be further investigated in other models.